Development of a novel cooking wine with high-efficiency deodorizing capability via a rapid fermentation strategy. (January 2022) - Fu, Chunyan; Wu, Dianhui; Jin, Zhao; Xie, Guangfa; Lu, Jian
Abstract: Chinese rice wine, when used as a cooking wine, has the important function of erasing fish and meat odours by evaporating odourous compounds and complementing the flavour of food. The objectives of the current study were to develop a short-term brewing process of rice wine and to evaluate the efficiency of deodorizing fish by preparing novel rice wine for cooking wine products. The technology of unilateral fermentation was applied in the rice wine brewing process, assisted by the pretreatment of enzymatic hydrolysis on rice. Following the optimization of enzymatic hydrolysis with ɑ-amylase, neutral protease, and glucoamylase, fermentation was conducted with Saccharomyces cerevisiae N85 and Lactobacillus plantarum B14. As a result, the primary fermentation period of rice wine was shortened from 15 days to 6 days. Furthermore, the preparation of cooking wine with sage, oregano, ginger, grape seed, and Chinese pepper was optimized through single-factor and response surface tests. The auxiliary material amount, extraction temperature, and extraction time were determined to be 1.61%, 35.8 °C, and 6 days, respectively. Finally, the cooking wine products exhibited 80.2%–88.9% deodorizing capability on 4 kinds of fish, which was more than 60% higher than that of common commercial cooking wines. Highlights: The optimal manufacturing process of a novel cooking wine was developed. The fermentation period of rice wine was shortened by 60% by rapid brewing strategy. The deodorizing ability of the developed cooking wine was enhanced by over 60%.